The first thousand days of life are the basis of metabolic programming. How to help with artifi cial feeding? - A. V. Polyanskaya; N. A. Geppe; S. N. Chebysheva; E. V. Frolkova; M. M. Chepurnaya; S. I. Shatalina (Лечащий Врач, 2023)
Background. The first year of a baby's life is a unique period. Growth rates at this age are very high. There is also intensive formation of the entire body, including the gastrointestinal tract; under these conditions, the process of formation of microbiota also occurs, which has a decisive influence on the digestibility of nutrients, the state of the immune system, nervous and other systems. This period of time provides the greatest opportunity to provide optimal nutrition for the normal development of the child, being, in fact, an open ″window of opportunity.″ The most important epigenetic factors that determine the expression of certain genes and, accordingly, human health are nutrition, stress, physical activity and the environment. Epigenetics is the science of the inherited properties of an organism that are not associated with changes in the actual nucleotide sequence of DNA and can be encoded not directly, but indirectly in the genome. Within the framework of the concept of nutritional programming, normalization of the body weight of the expectant mother and nutritious nutrition with sufficient amounts of macro- and micronutrients are extremely important factors determining the health of the child. Breastfeeding provides the best nutrition for the infant in terms of proper development and epigenetic effects. Breast milk has an optimal composition and maximum bioavailability of all its constituent substances. Unfortunately, there are a number of objective reasons that limit or make breastfeeding impossible. In such cases, the child is fed with adapted milk formulas based on cow's or goat's milk. For artificial feeding, it is necessary to choose modern, high-quality formulas that are as close as possible in composition to breast milk and selected individually, taking into account the child’s condition.   Results. According to many studies, goat's milk has some features that make it more similar to human milk, unlike cow's milk, and make the use of mixtures based on it attractive. Goat's milk, like human milk, contains exclusively A2 β-casein. The existing difference in the protein components of cow's and goat's milk contributes to easier digestion of mixtures based on goat's milk, facilitating the absorption of epigenetically significant nutrients. The milk formulas of the mixture based on goat's milk are enriched with a unique fat complex containing 42 % β-palmitate, which makes the digestibility of the mixtures even closer to breast milk. The process of metabolic programming is influenced by the state of the infant's intestinal microbiota. High levels of β-palmitate have a beneficial effect on the development of microbiota in formulafed infants and promote healthy metabolic programming. The most important prebiotic, substrate and carbon source for the growth of normal microflora in the infant’s intestines are breast milk oligosaccharides. The content of oligosaccharides in goat's milk is significantly lower than in women's milk (about 0.25-0.3 g/l), but higher than in cow's milk (0.03-0.04 g/l). Goat milk contains at least 14 oligosaccharides, some with molecular similarities, and 5 of them are completely identical to the oligosaccharides of breast milk and have similar beneficial effects. Thus, goat milk is an attractive natural source of oligosaccharides for the production of quality infant formulas.